Tax Clearance as an Administrative Instrument in the Dissolution of Cooperatives: Tax clearance sebagai Instrumen Administrasi dalam Upaya Pembubaran Koperasi - Damayanti, Suci; Devia Ardania, Vidya; Amanda Savira, Karina; Handoko, Sigit (Fakultas Hukum Universitas Jambi, 2026)
This study aims to provide a juridical analysis of the dissolution of cooperatives as legal entities in relation to the fulfillment of tax obligations, particularly concerning cooperatives that do not possess a Tax Identification Number and have failed to perform tax obligations since their establishment. The focus of this research lies in examining the normative tension between the cooperative law regime, which does not explicitly require tax compliance as a formal prerequisite for dissolution, and administrative practices that nevertheless require the settlement of outstanding tax obligations through a tax clearance mechanism. This research adopts a normative legal method employing a statutory approach and a case approach, with specific reference to the case of Cooperative “X” in Bantul Regency, Special Region of Yogyakarta. The findings demonstrate that the absence of an Tax Identification Number does not legally prevent the dissolution of a cooperative, yet it does not eliminate the cooperative’s status as a taxable legal subject, thereby causing all existing tax obligations to remain legally binding and subject to settlement, including potential administrative sanctions. This study affirms that tax clearance should not be regarded merely as an additional administrative requirement, but rather as an essential instrument of administrative law that ensures tax compliance, safeguards the state’s fiscal interests, and provides legal certainty in the process of dissolving cooperatives as legal entities.